Immunothrombosis as a bridge between innate immunity and hemostasis: A narrative review of emerging mechanisms - Anang Rizky Maulana; Cici Nuriah; Faradiyan Kencana (Indonesian Journal of Health Science, 2026)
Background: Immunothrombosis is an evolutionarily conserved host defense mechanism integrating innate immunity and hemostasis to limit pathogen dissemination through localized thrombus formation. While physiologically protective, dysregulated immunothrombosis contributes to thrombo-inflammatory diseases. Objective: This narrative review summarizes emerging cellular and molecular mechanisms linking innate immunity and coagulation, with emphasis on their pathological and therapeutic implications. Methods: A narrative literature review was conducted using Scopus-indexed journals retrieved from PubMed, Scopus, and ScienceDirect, prioritizing review articles and landmark original studies published between 2013 and 2025. Main Findings: Immunothrombosis is orchestrated by neutrophils, platelets, monocytes, endothelial cells, and complement systems through mechanisms including neutrophil extracellular trap (NET) formation, tissue factor expression, inflammasome activation, and immune–coagulation crosstalk. Conclusion: Immunothrombosis represents a fundamental biological bridge between innate immunity and hemostasis, offering novel therapeutic targets in thrombo-inflammatory disorders.